Quality-controlled datasets of Automatic Weather Station (AWS) at SIGMA-B site from 2012 to 2020: Level 1.2 ... - Nishimura, Motoshi; Aoki, Teruo; Niwano, Masashi; Matoba, Sumito; Tanikawa, Tomonori; Yamaguchi, Satoru; Yamasaki, Tetsuhide; Fujita, Koji (Arctic Data archive System (ADS), Japan, 2023)
Time-series data of an automatic weather station (AWS) operated at the SIGMA-B site on the Ice cap of Greenland since July 2012. The AWS measures the meteorological parameters every hour, which are air temperature, relative humidity, wind speed, wind direction, atmospheric pressure, shortwave radiation, longwave radiation, and snow height. his dataset (data level: 1.2) has been applied brief data masking procedures to eliminate anomalous values that violate physical laws or are impossible in the observed environment. Detailed information of the data level definition and versions are referred to "readme_SIGMA-B_Level_1.2.txt". It is strongly recommended to refer to "Dataset Revision Record" in the readme file and use the latest version of the dataset. ...